"I Just Absolutely Loved What I Did": The Rhetorical Construction of a Disabled Identity - Yvonne Stephens (Disability Studies Quarterly, 2011)
Siebers (2008) calls for a move beyond the social model of disability toward a "theory of complex embodiment" that allows for acknowledgment of the "negative" aspects of embodied disability and, in turn, allows for the adoption of a disabled identity. I answer Siebers' call by analyzing the discourse of one disabled individual—my father, a man with multiple sclerosis—and discussing his complex identity construction as a disabled person who sees the disability as a source of strength and knowledge as well as a source of suffering. Returning to that on which the social model is built—rhetoric—I argue that his rhetorical construction of a disabled identity is necessary and provides evidence for the need to step beyond the social model as currently conceived.
Keywords: Disability; discourse analysis; identity; multiple sclerosis; rhetoric; social model; theory of complex embodiment